Greenland and Canadian Arctic ice temperature profiles database - Løkkegaard, Anja; Mankoff, Kenneth David; Zdanowicz, Christian; Clow, Gary G.D.; Lüthi, Martin M.P.; Doyle, Samuel S.H.; Thomsen, Henrik Højmark; Fisher, David; Harper, Joel; Aschwanden, A.; Vinther, Bo Møllesøe; Dahl-Jensen, Dorthe; et al. (2023)
Here, we present a compilation of 95 ice temperature profiles from 85 boreholes from the Greenland ice sheet and peripheral ice caps, as well as local ice caps in the Canadian Arctic. Profiles from only 31 boreholes (36 %) were previously available in open-Access data repositories. The remaining 54 borehole profiles (64 %) are being made digitally available here for the first time. These newly available profiles, which are associated with pre-2010 boreholes, have been submitted by community members or digitized from published graphics and/or data tables. All 95 profiles are now made available in both absolute (meters) and normalized (0 to 1 ice thickness) depth scales and are accompanied by extensive metadata. These metadata include a transparent description of data provenance. The ice temperature profiles span 70 years, with the earliest profile being from 1950 at Camp VI, West Greenland. To highlight the value of this database in evaluating ice flow simulations, we compare the ice temperature profiles from the Greenland ice sheet with an ice flow simulation by the Parallel Ice Sheet Model (PISM). We find a cold bias in modeled near-surface ice temperatures within the ablation area, a warm bias in modeled basal ice temperatures at inland cold-bedded sites, and an apparent underestimation of deformational heating in high-strain settings. These biases provide process level insight on simulated ice temperatures. SCOPUS: ar.j info:eu-repo/semantics/published